2019
DOI: 10.1101/824649
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Co-inhibition of BCL-XL and MCL-1 with BCL-2 selective inhibitors A1331852 and S63845 enhances cytotoxicity of cervical cancer cell lines

Abstract: 34A combination of the BCL-2 inhibitors ABT-263 and A-1210477 inhibited cell proliferation 35 in the HeLa, C33A, SiHa and CaSki human cervical cancer cell lines. Drug sensitivity was 36 initially tested using 2-dimensional (2D) cell culture models. As ABT-263 binds to both BCL-37 2 and BCL-XL at high affinity, it was unclear whether the synergism of the drug combination 38 was driven either by singly inhibiting BCL-2 or BCL-XL, or inhibition of both. Therefore, we 39 used the BCL-2 selective inhibitor ABT-199 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Co-treatment with A-1331852 and S63845 induced rapid cell killing of these cell lines in vitro and in vivo models [22]. Our own study demonstrated that co-inhibition of MCL-1 and BCL-XL was crucial for killing cervical cancer cell lines [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-treatment with A-1331852 and S63845 induced rapid cell killing of these cell lines in vitro and in vivo models [22]. Our own study demonstrated that co-inhibition of MCL-1 and BCL-XL was crucial for killing cervical cancer cell lines [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Spheroids were generated as described previously [17]. Live-dead staining were conducted as described previously [18].…”
Section: Three-dimensional Spheroidsmentioning
confidence: 99%
“…Survivin is known to be highly expressed in most tumour cell types while being absent in normal cells, making it an excellent cancer therapeutic target [17]. Survivin protein suppresses caspase activation, resulting in the negative control of apoptosis or programmed cell death [18]. This has been shown by disrupting survivin induction pathways, which leads to an increase in apoptosis and a reduction in tumor development [19].…”
Section: Introductionmentioning
confidence: 99%